Assessment of clinical medical education needs inform design of a preceptor development program in Jordan: A multi method study - Soha Albeitawi; Mohammad Talal Al-zubi; Anas Aljaiuossi; Murad Shatnawi; Ahlam Al-Kharabsheh; Fadi Sawaqed; Emad Aborajooh; Walid I. Wadi; Randa Mahasneh; Benjamin Rowland Colton; Mohammad AlQudah; Tamara Kufoof; et al. (PLoS ONE, 2025)
Background Clinical preceptors serve as vital educators, so it is essential to enhance their effectiveness by developing a competency-based development program. In this study, we explored the challenges faced by preceptors and students, and measured the educational needs of preceptors, to inform the design of a syllabus for a preceptor development program. Methods This was a sequential multi method study utilizing a structured questionnaire survey and focus group discussions among a representative sample of medical students in their fourth, fifth, and sixth years in addition to preceptors from the six public medical schools in Jordan. Results Thematic analysis of focus group discussions revealed six themes: admission policy, training environment, curriculum gaps, trainers and mentorship, learners, and dissemination. The most important training needs documented by preceptors were teaching in the clinical setting, mentoring skills, simulation, assessment in the clinical setting, and providing feedback. Accordingly, a competency-based preliminary syllabus was developed. Conclusion It is essential to enrich the skills of preceptors regularly based on a needs assessment. Further long term studies are required to investigate the effectiveness of the proposed syllabus after implementation.